Pengaruh Biaya Pengendalian Ganoderma Terhadap Pendapatan Kelapa Sawit Petani Plasma di PT Mitra Aneka Rezeki Kubu Raya - Robertus, Ongki; Yurishintae, Erlinda; Hutajulu, Josua Parulian (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
One of the problems that often occurs at the research site is the Ganoderma fungus which attacks plasma farmers' oil palm trees. The symptoms include the leaves starting to turn yellow, the color of the leaves being pale and dull, growth slowing down, spots on the leaves, and the tree slowly falling due to the Ganoderma attack. The aim of the research is to find out how much the cost of controlling ganoderma on oil palm plants in the research area is and to analyze whether there is a difference in the average cost of controlling oil palm ganoderma before and after control. In this research the author chose a quantitative type of research. The data collection method used in this research was carried out by direct observation and interviews in the field using questionnaires as research instruments.. The number of samples used in this research was 30 farmers. The results of the study showed that the income of plasma farmers when ganoderma was not yet controlled was Rp1,853,000, and when ganoderma was controlled it was Rp2,197,900 which was obtained every time ganoderma was controlled, namely once every 6 months with a profit range of Rp. 344,900 for 1 hectare of land.